Broadband Light Generation in Nonlinear Silicon Nitride Strip-Loaded Lithium Niobate Waveguides - Raevskaia Marina; Della Torre Alberto; Grillet Christian; Boes Andreas; Mitchell Arnan; Monat Christelle (EPJ Web of Conferences, 2023)
This work demonstrates SiN strip-loaded lithium niobate waveguides with nonlinear optical properties, focusing on their performance when pumped at telecom wavelength. Experimental results show second and third harmonic generation in periodically poled SiN/LiNbO3. Furthermore, simulations reveal that these waveguides can be dispersion engineered to generate supercontinuum. The findings highlight the potential of SiN strip-loaded lithium niobate platform in sustaining broadband nonlinear light sources.